2000
DOI: 10.1007/s004670050799
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic syndrome associated with Kimura disease

Abstract: Kimura disease presents as benign subcutaneous swelling predominantly around the head and neck region. It has a high incidence of renal involvement. However, the pathogenesis of this association remains elusive. Only 2 pediatric cases and 11 adult cases of Kimura disease with renal involvement have been reported in the literature. In recent years many immunopathogenetic features suggesting an underlying T-cell and related cytokine defect have been noted in Kimura disease. We describe a unique case of an Asian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
125
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 12 publications
0
125
0
1
Order By: Relevance
“…3 Descriptions of Kimura's disease are limited in the English language pediatric literature. 4,5 Early diagnosis of Kimura's disease may spare the patient from potentially harmful and unnecessary invasive diagnostic procedures. We report a case of Kimura's disease in a young Asian male and review the literature.…”
mentioning
confidence: 99%
“…3 Descriptions of Kimura's disease are limited in the English language pediatric literature. 4,5 Early diagnosis of Kimura's disease may spare the patient from potentially harmful and unnecessary invasive diagnostic procedures. We report a case of Kimura's disease in a young Asian male and review the literature.…”
mentioning
confidence: 99%
“…Allergic reactions, infections, and autoimmune reactions with aberrant immune reaction have been suggested. 10 The findings of increased eosinophils, mast cells, and increased levels of interleukin 5 and IgE suggest an abnormal T-cell stimulation to a hypersensitivity-type reaction 11 . Molecular studies for immunoglobulin heavy-chain and T-cell receptor gene arrangement support a reactive nature.…”
Section: Discussionmentioning
confidence: 99%
“…Allergic reactions, infections, and autoimmune reactions with an aberrant immune reaction have been suggested in its etiopathogenesis [8]. A viral or parasitic trigger that may alter T-cell immunoregulation or induce an type-I hypersensitivity may result in release of eosinophiliotrophic cytokines [1,4,9]. The findings of increased eosinophils, mast cells, and levels of interleukin-5 and I g E suggest an abnormal T-cell stimulation to a hypersensitivity type reaction [9].…”
Section: Discussionmentioning
confidence: 99%
“…A viral or parasitic trigger that may alter T-cell immunoregulation or induce an type-I hypersensitivity may result in release of eosinophiliotrophic cytokines [1,4,9]. The findings of increased eosinophils, mast cells, and levels of interleukin-5 and I g E suggest an abnormal T-cell stimulation to a hypersensitivity type reaction [9]. Immuno-histochemical studies performed on skin, lymph nodes, and peripheral blood in Kimura's disease have shown marked proliferation of human leukocyte antigen-DR CD4 cells.…”
Section: Discussionmentioning
confidence: 99%